Project Manager to Project Motivator: Unlock the Secrets of Strengths-Based Project Management. - Pearce, Ruth (linkedin.com, 2021)
Learn to use your influence as a project manager for great project results. Discover the difference between managing and motivating and learn to build a culture of appreciation.